2008
DOI: 10.1001/archinte.168.21.2347
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Care Programs for Weight Management in Rural Communities

Abstract: Background: Rural counties in the United States have higher rates of obesity, sedentary lifestyle, and associated chronic diseases than nonrural areas, yet the management of obesity in rural communities has received little attention from researchers.Methods: Obese women from rural communities who completed an initial 6-month weight-loss program at Cooperative Extension Service offices in 6 medically underserved rural counties (n = 234) were randomized to extended care or to an education control group. The exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 233 publications
(178 citation statements)
references
References 40 publications
8
170
0
Order By: Relevance
“…Attendance was modest (i.e., 40–50%), which was similar to or slightly lower than attendance rates observed with other applied weight management programs. 1617, 21, 29 …”
Section: Discussionmentioning
confidence: 99%
“…Attendance was modest (i.e., 40–50%), which was similar to or slightly lower than attendance rates observed with other applied weight management programs. 1617, 21, 29 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that have had success with WLM have had longer-term interventions and support. 22,38,104 The trial comprised three arms: (1) an intensive intervention arm, (2) a less intensive intervention arm and (3) a control arm. We hypothesised that the intensive intervention would be effective and that the less intensive intervention would have an effect somewhere between the control and intensive intervention.…”
Section: The Weight Loss Maintenance In Adults Trial Interventionmentioning
confidence: 99%
“…For example, findings from the TOURS (Treatment of Obesity in Underserved Rural Settings) Trial (12) showed promising findings for a long-term, lifestyle intervention delivered through Extension offices in rural counties. However, the high dose of treatment in the TOURS Trial (i.e., 50 sessions over 18 months) poses a significant obstacle to implementation in rural communities.…”
Section: Introductionmentioning
confidence: 99%